The war behind the Eastern Front : the Soviet partisan movement in North-West Russia 1941 - 1944 - Hill, Alexander 1974- (Cass series on the Soviet (Russian) study of war, 2005)
The Soviet partisan movement and German occupation policy in Western, Soviet and post-Soviet writing -- The case study area : the rear areas of Army Group North -- Soviet and German preparations for occupation and resistance -- The establishment and nature of German military government -- The fledgling partisan movement -- Who was winning the partisan war during 1941? The military effectiveness of the partisan movement -- Life under German military government c. December 1941-spring/summer 1943 -- German 'anti-partisan' warfare and the civilian population -- The Soviet partisan movement comes of age -- The suppression of the adolescent partisan movement : partisan losses, the fragmentation of units and forced withdrawal to Soviet lines -- Evacuation, scorched earth, and the emergence of a 'vsenarodnoe' partisan movement 1963